Consideration of range-wide variation is critical when splitting widely distributed species: the case of the proposed Iguana melanoderma - Burg, Matthijs P. Van Den; Queiroz, Kevin De; Ventayol, Marina; Debrot, Adolphe O.; Malone, Catherine L. (Zootaxa, 2026)
Among Iguaninae species, Iguana iguana (Linnaeus) has the largest geographic range, spanning most of the Neotropical mainland and numerous islands including several in the Lesser Antilles. Genetic data indicated the presence of cryptic diversity and at least four major, mtDNA clades. However, rather than assessing the taxonomic status of these four major clades, recent taxonomic work has focused more narrowly on populations in the Lesser Antilles nested deeply within one major clade. In one such case, melanistic populations on Saba, Montserrat, and in northern Venezuela have been proposed as Iguana melanoderma Breuil et al. Here we re-evaluate the taxonomic status of I. melanoderma within the broader context of the I. iguana species complex. We generated museomic data from 10 specimens collected as early as 1929 from 10 new localities across northern Venezuela, and two samples from Trinidad, resulting in eight previously unknown ND4 haplotypes. We conducted divergence comparisons and phylogenetic analyses using mtDNA sequences. Our results indicate that the previously reported genetic distinctiveness of I. melanoderma was over-estimated due to limited geographic sampling. Instead, genetic data from northern South America reveal an eroded distinction and shallow divergences among sampled populations of the I. iguana species complex (Clade IV), including the proposed Iguana melanoderma. Numerous sampling gaps remain in this region of northern South America, which hamper taxonomic interpretations of current genetic data. Beyond genetics, the morphological dataset underlying the description of I. melanoderma was geographically limited and lacked data from crucial populations. We argue that, for the present, I. melanoderma should not be recognized but instead should be considered part of I. iguana (Clade IV), and we highlight the importance of broader sampling efforts in future taxonomic research on this species complex as well as the necessity of considering range-wide variation in taxonomic studies of wide-ranging taxa more generally.